1996
DOI: 10.1037/0735-7044.110.6.1321
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress impairs rat spatial memory on the Y maze, and this effect is blocked by tianeptine treatment.

Abstract: Chronic restraint stress causes significant dendritic atrophy of CA3 pyramidal neurons that reverts to baseline within a week. Therefore, the authors assessed the functional consequences of this atrophy quickly (within hours) using the Y maze. Experiments 1-3 demonstrated that rats relied on extrinsic, spatial cues located outside of the Y maze to determine arm location and that rats with hippocampal damage (through kainic acid, colchicine, or trimethyltin) had spatial memory impairments. After the Y maze was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
441
5
11

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 673 publications
(475 citation statements)
references
References 90 publications
18
441
5
11
Order By: Relevance
“…Moreover, we found that such a stressor regimen caused significant decreases in dendritic spine density in dendrites of the granule cells in the anterior (or dorsal) dentate gyrus at 6 hours after the conclusion of the stressor regimen. Although chronic stress has been known to produce long-lasting dendritic atrophy in hippocampus [38], a 1-hr platform stress was also reported to cause immediate morphological changes in hippocampus [39]. In parallel with the latter report, our findings indicated that a robust stressor may indeed render morphological changes in the existing granule cells in hippocampal dentate gyrus.…”
Section: An Acute Intense Stressor Causes Rapid Morphological Changesupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, we found that such a stressor regimen caused significant decreases in dendritic spine density in dendrites of the granule cells in the anterior (or dorsal) dentate gyrus at 6 hours after the conclusion of the stressor regimen. Although chronic stress has been known to produce long-lasting dendritic atrophy in hippocampus [38], a 1-hr platform stress was also reported to cause immediate morphological changes in hippocampus [39]. In parallel with the latter report, our findings indicated that a robust stressor may indeed render morphological changes in the existing granule cells in hippocampal dentate gyrus.…”
Section: An Acute Intense Stressor Causes Rapid Morphological Changesupporting
confidence: 79%
“…Dendritic spine density of the pyramidal cells in the hippocampal CA3 region has been identified to closely associate with the Y maze performance in rats [38]. In this study, we found that neither the stressor regimen nor the presence of companions affected mouse Y maze performance.…”
Section: The Presence Of Companions Prevents the Stressor-induced Decmentioning
confidence: 47%
“…A zero score indicates chance performance with no arm preference. Total entries (sum of entries into all three arms) were also used to determine whether motor or motivational factors differed among the groups (Conrad et al, 1996).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In male rats, restraint for 6 h/day/21 days retracts hippocampal dendritic arbors in the CA3 region (Watanabe et al, 1992c;Magarinos and McEwen, 1995a;Magarinos et al, 1998;Conrad et al, 1999), which corresponds to impaired hippocampal-dependent spatial memory (Luine et al, 1994a,b;Conrad et al, 1996). Pharmacological blockade of CA3 dendritic retraction also correlates with the prevention of spatial memory deficits in separate studies (Watanabe et al, 1992a,b;Luine et al, 1994a,b;Conrad et al, 1996). In contrast, chronically-stressed, gonadally-intact females have less robust dendritic retraction in basal CA3 dendrites compared with the apical CA3 dendritic retraction seen in males (Galea et al, 1997).…”
mentioning
confidence: 99%
“…Accordingly, tianeptine has particularly favorable effects on cognitive functions and the positive effect of tianeptine may be mediated, at least in part, through its upregulation of neurogenesis and dendrite remodeling. Thus, tianeptine blocks the dendritic remodeling caused by stress or glucocorticoids, 51,52 blocks stress-induced impairments of spatial memory performance in radial and Ymaze, 93,94 and antagonizes the deleterious effects of alcohol. 95 Yet, tianeptine effects can also be rapid.…”
Section: Procognitive Effectsmentioning
confidence: 99%